(untitled) (AUN INTERNATIONAL CONFERENCE, 2024)
Many studies have been carried out to investigate the factors affecting college students’ academic performance. The main purpose of this study is to gain an understanding on the academic factors affecting the academic performance of information systems (IS) students in Nigeria. The success rate of IS student in Nigeria universities is low compared to universities outside Nigeria. The number of universities that offer IS as a major are few, a developing country like Nigeria is yet to understand the importance of IS. Therefore, people pay little or no attention to that field of study, which creates countless factors that could affect the IS. The survey methodology was used to study the academic factors affecting the success of IS students in Nigeria universities. A structured survey questionnaire was used to generate data. Statistical Package for the Social Sciences (SPSS) was used as a tool for the data analysis. The results of this study offer an important insight into the academic factors that affect the academic performance of students in the department of IS at undergraduate level.